THE INFLUENCE OF COMPETENCY AND TRAINING ON PERFORMANCE WITH WORK MOTIVATION AS INTERVENING VARIABLE - Aprianes Wijaya; Mulyanah Mulyanah; Rokiah Kusumapradja (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
This study is focused on the dynamics of service quality issues in 2020–2021, which highlight issues with inpatient nurses' patient care performance. This study aimed to gather proof of the connection between competence and training and nursing performance, with job motivation as an intermediary variable. A cross-sectional study involving 135 inpatient nurses was used in the research design using a straightforward random sampling method. The sampling strategy used probability and saturation samples to sample the complete population. The study's findings demonstrate that competency and training have a direct, favorable, and significant impact on work motivation and performance and that work motivation positively mediates the relationship between competency and training and nurse performance. That performance directly favors and significantly impacts work motivation. If there is work motivation, competence, and training can be higher to improve nurse performance.